X-efficiency and Its Determinants of Beijing, Shanghai, and Shenzhen Banks - Li, Ruijue (2018)
This paper explores the efficiency of 52 commercial banks in three cities of China (Beijing, Shanghai, and Shenzhen) over the period of 201 - 2017, using the parametric Stochastic Frontier Analysis approach. Then, fixed and random effects models were used to evaluate the impact of internal and external factors on the banks’ cost efficiency scores. The results indicate that efficiency has maintained a relatively high level over 98% in three cities, and Shanghai banks seems to be slightly more efficient than banks in other two cities. However, the location of banks does not necessarily affect the efficiency cores. In line with many established literature on China, foreign banks appear to be more efficient than the domestic counterparts, and large state-owned banks are not the most efficient player in financial market. In the second-stage analysis, GDP growth rate suggests no statistically significant impact on banking efficiency, while both the unemployment rate and the inflation rate have a significantly negative influence on bank cost efficiency. As for bank-specific factors, there is no statistically explicit association between bank size and cost efficiency, while the capital ratio seems to have a weak and negative effects on the cost efficiency of banking sector.